Clinical Validation of the QMAC-DST System for Testing the Drug Susceptibility of Mycobacterium tuberculosis to First- and Second-Line Drugs - Lee, Sangyeop; Chu, Daehyun; Choi, Youn Mi; Jo, EunJi; Kim, Suyeoun; Kim, Haeun; Kim, Hyun Jung; Chang, Jeonghyun; Sung, Heungsup; Kang, Geumrae; Jin, Bonghwan; Kim, Eun-Geun; et al. (Frontiers in Microbiology, 2019)
There is a high demand for novel approaches to counter the various challenges of conventional drug susceptibility testing (DST) for tuberculosis, the most prevalent infectious disease with significant global mortality. The QMAC-DST system was recently developed for rapid DST using image technology to track the growth of single cells of Mycobacterium tuberculosis (MTB). The purpose of this study was to clinically validate the QMAC-DST system compared to conventional DST. In total, 178 MTB isolates recovered from clinical specimens in Asan Medical Center in 2016 were tested by both QMAC-DST and absolute concentration methods using Lowenstein-Jensen media (LJ-DST). Among the isolates, 156 were subjected to DST using BACTEC MGIT 960 SIRE kits (BD, Sparks, MD) (MGIT-DST). The susceptibility/resistance results obtained by QMAC-DST were read against 13 drugs after 7 days of incubation and compared with those of LJ-DST. Based on the gold standard LJ-DST, the agreement rates of QMAC-DST for all drugs were 97.8%, 97.9%, and 97.8% among susceptible, resistant, and total isolates, respectively, while the overall agreement of MGIT-DST tested for 156 isolates against first-line drugs was 95.5%. QMAC-DST showed the highest major error of 6.4% for rifampin; however, it could be corrected by a revised breakpoint since false-resistant isolates showed growth of only half of the true-resistant isolates. The rapid and accurate performance of QMAC-DST warrants ideal phenotypic DST for a wide range of first-line and second-line drugs.